Pathways for Breaking Through the Dilemmas of Vocational Education in China from the Perspective of Artificial Intelligence Empowerment - Shi, Yao; Lyu, Zhongyi (Innovative Applications of AI, 2025)
Against the backdrop of the rapid development of artificial intelligence technology, vocational education in China is facing deep-seated contradictions stemming from the structural mismatch between talent supply and industrial demand. These challenges are further exacerbated by social cognitive biases, uneven resource distribution, and outdated teaching models. This study systematically examines the historical evolution, scale characteristics, and current challenges of vocational education. At the same time, it draws on the successful application experiences of AI in basic education and higher education, and proposes several innovative solutions centered on AI technology, aiming to construct a theoretical framework for the deep integration of vocational education and AI technology, break through development bottlenecks, and promote the transformation of vocational education from scale expansion to connotation improvement in the digital economy era.